Reog Ponorogo Art from the Perspective of Islamic Law: A Maqâshid al-Syarî‘ah Analysis of Ritual and Aesthetic Aspects - Nurul Iman; Katni Katni; Hardivizon Hardivizon (Madania: Jurnal Kajian Keislaman, 2026)
Reog Ponorogo is a traditional performing art that combines ritual practices and aesthetic expressions within Muslim society, raising debates concerning creed, worship, and morality in Islamic law. This study examines the ritual and aesthetic dimensions of Reog Ponorogo through the framework of maqâshid al-syarî‘ah and explores their implications for the development of traditional arts in Muslim communities. Employing a qualitative normative–empirical approach, the study draws on in-depth interviews with dancers, musicians, and Reog practitioners, complemented by direct observation of performances and ritual practices. The data were analyzed normatively using the principles of maqâshid al-syarî‘ah to evaluate the compatibility of Reog practices with the objectives of Islamic law. The findings demonstrate that Reog rituals cannot be generalized under a single legal status. Rituals involving supplication to entities other than God, such as offerings (sesaji), contradict the principle of ḥifẓ al-dîn and therefore require reconstruction or elimination, whereas rituals functioning as psychological and spiritual preparation may be regarded as conditionally mubâḥ. From an aesthetic perspective, music, dance, and costumes are generally permissible provided that they observe standards of modesty and Islamic moral values. This study contributes to contemporary Islamic legal discourse by offering a contextual maqâshid -based framework for evaluating local cultural practices, showing that traditional arts can be reconstructed in ways that preserve cultural identity while remaining consistent with Islamic legal principles. Seni Reog Ponorogo merupakan kesenian tradisional yang memadukan praktik ritual dan ekspresi estetika dalam masyarakat Muslim, sehingga menimbulkan perdebatan terkait akidah, ibadah, dan moralitas dalam hukum Islam. Penelitian ini bertujuan untuk menganalisis dimensi ritual dan estetika seni Reog Ponorogo melalui kerangka maqâshid al-syarî‘ah serta mengkaji implikasinya terhadap pengembangan seni tradisional di masyarakat Muslim. Penelitian ini menggunakan pendekatan kualitatif normatif-empiris dengan memanfaatkan wawancara mendalam terhadap penari, musisi, dan penggiat Reog, serta observasi langsung terhadap pertunjukan dan praktik ritual. Data dianalisis secara normatif menggunakan prinsip-prinsip maqâshid al-syarî‘ah untuk menilai kesesuaian praktik Reog dengan tujuan hukum Islam. Hasil penelitian menunjukkan bahwa ritual dalam Reog Ponorogo tidak dapat digeneralisasi dalam satu status hukum. Ritual yang mengandung permohonan kepada selain Allah, seperti sesaji, bertentangan dengan prinsip ḥifẓ al-dîn sehingga perlu direkonstruksi atau dieliminasi, sedangkan ritual yang berfungsi sebagai persiapan psikologis dan spiritual dapat dipandang sebagai mubâḥ dengan syarat tertentu. Dari aspek estetika, musik, tarian, dan kostum pada dasarnya diperbolehkan selama tetap menjaga kesopanan dan nilai-nilai moral Islam. Penelitian ini berkontribusi pada pengembangan diskursus hukum Islam kontemporer dengan menawarkan kerangka evaluasi budaya lokal berbasis maqâshid yang kontekstual, sehingga seni tradisional dapat direkonstruksi tanpa menghilangkan identitas budaya lokal dan tetap selaras dengan prinsip-prinsip hukum Islam.